If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 5y = 2 Solving -1x + 5y = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5y' to each side of the equation. -1x + 5y + -5y = 2 + -5y Combine like terms: 5y + -5y = 0 -1x + 0 = 2 + -5y -1x = 2 + -5y Divide each side by '-1'. x = -2 + 5y Simplifying x = -2 + 5y
| V^2+12+35= | | 13(5-2x)=-13(4x+1)-8x | | 9y+3y+48=180 | | 9x+3=2x+15 | | 7-2n=n-24 | | 3/5(10x-15)=27 | | 5-3(2x-7)=4(x+5)-6 | | -12+4(-3-x)=32-49 | | (5x+3y)(5x-3y)= | | 1.666d+.666=.25(d-2) | | 8x+3.1=-6+14.3 | | 1.666d+666=.25(d-2) | | 43+x=7 | | 14+2(y+3000)=1340 | | -49=6x-13-4c | | d+32=1400 | | -0.8=.13x-.21x | | 30+3y-7=10y-12-2y | | 4x+2+2x=4x+4x | | f-11=987 | | 1.666+.666=.25(d-2) | | x+6x=46207 | | 2x+y+10x-4y=180 | | 99x=3 | | 0=4x^3-6x^2+1 | | by+2=c | | 36-4=-13 | | -3(4m+3)-5=-30-8m | | y^2-6x+27=0 | | x+19+3x=-5-3x-11 | | 4w+9=9w-7 | | A=4(3.14r^2) |